In-vitro anti-microbial and brine-shrimp lethality potential of the leaves extract of nahar (Mesua ferrea) plant - Adewale, Ahmed Idris; Mirghani, Mohamed Elwathig Saeed; Muyibi, Suleyman Aremu; Daoud, Jamal Ibrahim; Abimbola, Mikail Maryam (2011)

(untitled)
The growing interest in human health and increasing bacterial resistance to antibiotics among other reasons have resulted into an increasing need for the exploration of both the essential oils and other plant extracts in the food and pharmaceutical industries. This work, as part of on-going work on the leaves of Nahar (Mesua ferrea) plant, was aimed at evaluating the antimicrobial activity, minimum inhibitory concentration as well as the cytotoxicity of the leaves extract. The dry leaves were grinded and extracted in an oven shaker set at 37°C and 200rpm for 24 hours using ethanol and methanol as solvents. The agar disc diffusion method was used for the evaluation of antibacterial property of the leaves extract, micro broth dilution was employed for the determination of minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC), while Brine shrimp (Artemia salina) lethality bioassay was made use of for the cytotoxicity assay. Ethanol gave higher extract’s yield (6.20%) than methanol. The extract showed a remarkable antibacterial property against all the selected microbes (Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis and Staphylococcus aureus) with the inhibition zones ranging from 16.0±0.5mm to 18.0±0.5mm for all the tested bacteria. The MIC range of 2.5- 0.625 mg/ml with MBC value of 5mg/ml was obtained for the gram-negative bacteria while MIC rangeof 1.3- 0.313mg/ml with MBC value of 2.5mg/ml was obtained for the gram-positive bacteria. The leaves extract was found to be toxic to the Brine shrimps with LC50 of 500ppm (μg/ml) suggesting that the extracts may contain bioactive compounds of potential the therapeutic and prophylactic significance.